Clinical, Paraclinical Characteristics and Treatment Response in Children with Nephritis Caused by Systemic Lupus Erythematosus - Dem, Pham Van; Nam, Nguyen Thanh; Kien, Pham Trung (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 34 No 1DO - 10.25073/2588-1132/vnumps.4089, 2018)
The study describes the clinical, paraclinical characteristics and treatment response in children with nephritis caused by systemic lupus erythematosus. Subjects of study: 32 children with systemic lupus erythematosus were hospitalized from June 1, 2016 to May 30, 2017 in the Pediatrics Department, Bach Mai Hospital. Methodology: Description. Results: The average age of disease was 10.2 ± 1.5 years [22 months - 15 years]. The prevalence and incidence rates of SLE were higher in girls (88.4%) than in boys (13.6%), and girl/boy ratio was 6.4/1. Facial and peripheral edema was the most common symptom (87.5%), butterfly rash (43.7%). Skin rash and fiver were 53.1%, long fiver - 40.3% and hypertension - 37.5%. Central nervous injury was found at 12.5%. The paraclinical aspects showed that 100% of the patients were positive with the anti-nuclear antibody and the anti-double stranded DNA (anti-dsDNA) antibody. Low complement C3/C4 and nephrotic proteinuria were 93.7%, acute renal injury – 37.5%. The post 6-month treatment outcomes showed that 62.6% of the patients had complete remission and the mortality rate was 9.3% (3 patients, because of their withdrawal from treatNephritis in children, Systemic Lupus Erythematosus.ment). Conclusions: The clinical manifestations of systemic nephritis caused by lupus erythematosus in the children were severe but responded well to treatment.  Keywords Nephritis in children, Systemic Lupus Erythematosus. References [1] Linda T. Hiraki,Candace H. Feldman, Jun Liu, et al, Prevalence, Incidence, and Demographics of Systemic Lupus Erythematosus and Lupus Nephritis From 2000 to 2004 Among Children in the US Medicaid Beneficiary Population, ARTHRITIS & RHEUMATISM, 64(8), (2012), 2669. [2] Robecca M. Lombel, Elisabeth M. Hodson, Debbie S. Gipson, Treatment of lupus nephritis syndrome in children: new guidelaines from KDIGO. Pediatr Nephrol, 2304 (8), (2012), 221. [3] Edworthy, S. M., Zatarain, E., McShane, D. J., Bloch, D. A, Analysis of the 1982 ARA lupus criteria data set by recursive partitioning methodology: new insights into the relative merit of individual criteria, J Rheumatol, 15(10), (1998), 1493. [4] Hui-Kim Yap, Nephritis in systemic lupus erythematosus,Pediatric Nephrology, Second Editor, (2015), 240-249. [5] Sulaiman M, Al-Mayouf,Systemic lupus erythematosus in Saudi children: long-term outcomes, 36(2), (2017), 343. [6] Chagas Medeiros MM, Bezerra MC, Braga FN et al,Clinical and immunological aspects and outcome of a Brazilian cohort of 414 patients with systemic lupus erythematosus (SLE): comparison between childhood-onset, adult-onset, and late-onset SLE, Lupus,2 5(4), (2016), 355. [7] Thái Thiên Nam, Đặc điểm lâm sàng, mô bệnh học và đánh giá kết quả điều trị ban đầu bệnh Lupus ban đỏ hệ thống ở trẻ em Bệnh viện Nhi trung ương, Tạp chí Nhi khoa, 4(2), (2011),57. [8] Trần Hữu Minh Quân, Phạm Nam Phương, Huỳnh Thoại Loan, Đặc điểm viêm cầu thận màng do Lupus tại Bệnh viện Nhi đồng I, Hội nghị khoa học Nhi khoa toàn quốc lần thứ 22, (2015), 108. [9] Bahar Artim-Esen, Sezgin Şahin, Erhan Çene, et al, Comparison of Disease Characteristics, Organ Damage, and Survival in Patients with Juvenile-onset and Adult-onset Systemic Lupus Erythematosus in a Combined Cohort from 2 Tertiary Centers in Turkey”. J Rheumatol, 36(1), (2017), 1. [10] Fatemi A, Matinfar M, Smiley A,Childhood versus adult-onset systemic lupus erythematosus: long-term outcome and predictors of mortality, Clin Rheumatol, 45(3), (2017), 233.